Executorial Power on Certificate of Liability Based on Credit Agreement - Agnis Nova Della (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The Mortgage Certificate has executorial power in the credit agreement at Bank Mandiri of Semarang City and to identify and examine obstacles in the execution and solutions. This theoretical framework is using the theory of Progressive Theory, Theory of Law Enforcement, Theory of Islamic Justice. The research method was used to obtain data in this study, using an empirical juridical approach, with descriptive analysis research specifications. The results of this study are: (1) The executive power possessed by the Mortgage Certificate is the same as the court's decision which has permanent legal force, this is because the Mortgage Certificate has included an title which reads